Multicentric neoadjuvant pilot Phase II study of cetuximab combined with docetaxel in operable triple negative breast cancer. Issue 9 (28th December 2015) - Nabholtz, J.M.; Chalabi, N.; Radosevic‐Robin, N.; Dauplat, M.M.; Mouret‐Reynier, M.A.; Van Praagh, I.; Servent, V.; Jacquin, JP; Benmammar, K.E.; Kullab, S.; Bahadoor, M.R.K.; Kwiatkowski, F.; et al.
Abstract : Systemic therapy for triple negative breast cancer (TNBC) is mostly based upon chemotherapy. Epithelial Growth Factor Receptor (EGFR) is overexpressed in around 50% of TNBC and may play a role in its pathogenesis. Consequently, we performed a multicentric pilot Phase II neoadjuvant trial of cetuximab (anti‐EGFR antibody) combined with docetaxel for patients with operable, Stage II–III TNBC. Therapy consisted of weekly cetuximab (first infusion: 400 mg/m 2, then 250 mg/m 2 ) combined with six cycles of docetaxel (T: 100 mg/m 2 ) q.3 weeks. Subsequently, all patients underwent surgery. The primary endpoint was pathological complete response (pCR) while clinical response, toxicity and ancillary studies were secondary endpoints. Paraffin‐embedded and frozen tumor samples were systematically collected in order to identify predictive biomarkers of efficacy and resistance. From a total of 35 accrued patients, 25 were assessable for pathologic response. The pCR rate was 24% [95% CI: 7.3–40.7]. Complete clinical response rate (cCR) was observed in 22% of cases. Conservative surgery was performed in 75% of patients. Toxicity, mostly cutaneous and hematologic, was manageable. The pre‐therapy ratio between CD8+ and FOXP3+ tumor‐infiltrating lymphocytes equal or higher than 2.75 was predictive of pCR: 43% versus 0%, p = 0.047. Cetuximab in combination with docetaxel displays a modest activity, but acceptable toxicity as neoadjuvant therapy of operable TNBC. Similarly to previous observations using panitumumab, another anti‐EGFR antibody, the immune component of the tumor microenvironment may play an important role in predicting TNBC response to the neoadjuvant therapy. Abstract : What's new? Systemic therapy for triple negative breast cancer (TNBC) is mostly based upon chemotherapy. Epithelial Growth Factor Receptor (EGFR) is however overexpressed in around 50% of TNBC and may play a role in its pathogenesis. Here, the authors performed a multicentric pilot phase II neoadjuvant trial of cetuximab (anti‐EGFR antibody) combined with docetaxel for patients with operable, stage II‐III TNBC. In this first trial of docetaxel plus cetuximab in neoadjuvant therapy, the combination appears modestly efficacious, but manageable in terms of toxicity. The immunologic component of the tumor environment may potentially be used as a predictor of the therapy efficacy.